Fake Chinese sounds - Tsong, Jing Jing (Kokila, an imprint of Penguin Random House LLC, 2024)
"Between homework, studying, and Chinese school, Měi Yīng's summer is shaping up to be a boring one. Her only bright spots are practice with her soccer team, the Divas, and the time spent with her năi nai, who is visiting from Taiwan. Although Měi Yīng's Mandarin isn't the best and Năi Nai doesn't speak English, they find other ways to connect, like cooking guōtiē together and doing tai chi in the mornings. By the end of the summer, Měi Yīng is sad to see Năi Nai go-she's the complete opposite of Měi Yīng serious professor mother-but excited to start fifth grade. Until new kid Sid starts making her the butt of racist jokes. Her best friend, Kirra, says to ignore him, but does everyone else's silence about the harassment mean they're also ignoring Sid . . . or her? As Sid's bullying fuels Měi Yīng's feelings of invisibility, she must learn to reclaim her identity and her voice."--Page 4 of cover.